The contemporary press of Holland. [With contribs of M. Rooij, E. Diemer, N. Cramer, a.o.]
De Journalist. Forthnightly of the Federatie van Nederlandse Journalisten. 1961, april. Published on the occasion of the Conference of the Executive of the International Federation of Journalists from April 10-14, 1961.